2006
DOI: 10.1080/10428190600687547
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin's lymphomas with Burkitt-like cells are associated with c-Myc amplification and poor prognosis

Abstract: Out of 344 patients with newly diagnosed non-Hodgkin's lymphoma (NHL), this study identified 16 patients presenting Burkitt-like cells (BLCs) after cytological and/or histological review. Conventional cytogenetic analysis showed at diagnosis complex chromosomal abnormalities in 13 cases and a normal karyotype in three cases. However, neither t(8;14)(q24;q32) nor the variants t(2;8)(p12;q24) or t(8;22)(q24;q11) was detected. FISH studies showed c-MYC amplification in all cases with four to more than seven copie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 23 publications
1
40
1
1
Order By: Relevance
“…30 Gains were considered when three or four copies of the gene studied were identified, whereas more than four copies were considered as amplifications. 31 However, as we did not use a centromer probe in this study, we cannot distinguish between true polysomies and partial chromosomal gains.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…30 Gains were considered when three or four copies of the gene studied were identified, whereas more than four copies were considered as amplifications. 31 However, as we did not use a centromer probe in this study, we cannot distinguish between true polysomies and partial chromosomal gains.…”
Section: Methodsmentioning
confidence: 91%
“…Mossafa et al also reported that MYC amplification was an unfavorable alteration in a group of patients with highgrade B-lymphomas, including 12 with transformed lowgrade B-cell lymphomas and three DLBCL. 31 MYC rearrangements have been detected in 6 to 14% of de novo DLBCL. In our study, 12 (7%) cases showed MYC rearrangement and 7/12 (58%) had additional rearrangements of BCL2 and/or BCL6.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms such as amplification or deregulation by juxtaposition of MYC with other genes might also lead to MYC overexpression and as a result a BL-like morphology. 51,52 Non-IG-MYC translocation may occur as a secondary event (for example, in follicular lymphoma), resulting in a transformed lymphoma with a BL-like morphology. 53 Although the numbers were small, we compared the genetic profile of the 13 BL with a non-IG-MYC breakpoint with that of the core subset.…”
Section: Bl With a Non-ig-myc Translocation (Bl Non-ig-myc) Is A Rarementioning
confidence: 99%
“…13 Nevertheless, the proper classification of a tumor as BL or DLBCL is of paramount importance, as these tumors exhibit distinct biological behaviors and are treated with different chemotherapeutic regimens. 11,[14][15][16] Recently, it has become apparent that rare cases of DLBCL lacking the morphological and/or immunophenotypic features of BL can harbor a c-MYC translocation (MYC + DLBCL). 17 These tumors respond poorly to conventional, DLBCL-based chemotherapeutic regimens and might, therefore, be considered for BL-type regimens in the future.…”
Section: Introductionmentioning
confidence: 99%